Multi person decision making – A compromise solution - Garisch, Isabelle (South African Statistical Journal, 2016)
In this paper a group of l decision makers who are confronted by the problem of choosing a mutually acceptable solution to a statistical decision problem, is considered. If consensus is not reached, a solution through compromise is called for. A measure of similarity or agreement between each pair of decision makers is defined, where this measure can be used to assign weights to the decision makers. These weights give an indication of the importance of the decision makers in terms of relative agreement with others in the group. A solution through compromise can be found by using these weights in the calculation of a randomised decision.